A task model for supporting virtual laboratory based on inquiry skills, social and scientific communication - Siska Desy Fatmaryanti; Umi Pratiwi; Raden Wakhid Akhdinirwanto; Dwi Sulisworo (Institute of Advanced Engineering and Science, 2022)
Comprehensive monitoring in virtual laboratory learning needs a task model. This model was design based on inquiry skills, social and scientific communication of prospective physics teachers. The development of these three skills is still a problem in recent research on virtual laboratory learning. This research was research and development (RD) using a preliminary study (literature studies, field surveys, and preparation of the initial product) and development of the model (within limited testing). Respondents were 54 prospective physics teachers and five physics lecturers from several universities in Indonesia. The analysis was done by descriptive qualitative, and quantitative. There are two essential parts of the task model. The first part consists of six inquiry steps, which describe the interactions between students with their virtual experiments. The second part consists of three inquiry steps that analyze how students communicate their virtual experiments through verbal, picture, and diagrammatic representations. Based on these findings, the task model's design is essential to develop inquiry skills, social and scientific communication for prospective physics teachers. The researcher can use this task model in the next step of RD.